MORAL REASONING AND DISCOURSE FRAGMENTATION IN YOUTUBE COMMENTS ON SEXUAL VIOLENCE CASES INVOLVING RELIGIOUS AUTHORITY - Damayanti, Annisa; Syukriyansyah (Communication Science Department - Faculty of Social and Political Sciences, Universitas Satya Negara Indonesia (USNI), 2025)
This study examines moral reasoning and discourse fragmentation within the YouTube comment section of a viral video detailing a case of sexual violence involving a religious authority figure in Indonesia. Employing a Mixed Methods Social Network Analysis (MMSNA) approach, we analyzed 6,018 comments from 5,484 users to map the network structure, identify communicative communities, and assess emotional polarization via sentiment analysis. Findings reveal a highly fragmented and sparse network with low user interactivity, dominated by isolated, small-scale communities. Despite this structural fragmentation, sentiment analysis showed a predominance of neutral expressions (76.9%), with limited emotional polarization between the six main thematic communities identified. These communities function as distinct